The divergence and positive selection of the plant‐specific BURP‐containing protein family - Wang, Lihui; Wu, Ningning; Zhu, Yan; Song, Wanlu; Zhao, Xin; Li, Yaxuan; Hu, Yingkao (Ecology and evolution, 2015)
BURP domain‐containing proteins belong to a plant‐specific protein family and have diverse roles in plant development and stress responses. However, our understanding about the genetic divergence patterns and evolutionary rates of these proteins remain inadequate. In this study, 15 plant genomes were explored to elucidate the genetic origins, divergence, and functions of these proteins. One hundred and twenty‐five BURP protein‐encoding genes were identified from four main plant lineages, including 13 higher plant species. The absence of BURP family genes in unicellular and multicellular algae suggests that this family (1) appeared when plants shifted from relatively stable aquatic environments to land, where conditions are more variable and stressful, and (2) is critical in the adaptation of plants to adverse environments. Promoter analysis revealed that several responsive elements to plant hormones and external environment stresses are concentrated in the promoter region of BURP protein‐encoding genes. This finding confirms that these genes influence plant stress responses. Several segmentally and tandem‐duplicated gene pairs were identified from eight plant species. Thus, in general, BURP domain‐containing genes have been subject to strong positive selection, even though these genes have conformed to different expansion models in different species. Our study also detected certain critical amino acid sites that may have contributed to functional divergence among groups or subgroups. Unexpectedly, all of the critical amino acid residues of functional divergence and positive selection were exclusively located in the C‐terminal region of the BURP domain. In conclusion, our results contribute novel insights into the genetic divergence patterns and evolutionary rates of BURP proteins. BURP domain‐containing proteins belong to a plant‐specific protein family, and have diverse roles in plant development and stress responses. The absence of BURP family genes in unicellular and multicellular algae suggests that this family (1) appeared when plants shifted from relatively stable aquatic environments to land, where conditions are more variable and stressful, and (2) is critical in the adaptation of plants to adverse environments. All of the critical amino acid residues of functional divergence and positive selection were exclusively located in the C‐terminal region of the BURP domain.